Penyuluhan Pengelolaan Keuangan Rumah Tangga Di Masa Pandemi Covid-19 Di Kampung Buaran Cakung Jakarta Timur - Muhamad Akbar; Anita Maulina; Vivi Chifziah (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
The Covid-19 pandemic that occurred in Indonesia created instability and a crisis in the economic sector, especially the household sector.  As the main support for the economy, household consumption slowed down significantly, which greatly affected the performance of industry and UMKM businesses.  Household financial management is one of the solutions so that the use of economic resources, especially finance, can be planned, implemented, monitored, evaluated and controlled to ensure the stability and economic growth of the family.  The lack of knowledge of housewives, difficulty in determining priorities for daily needs, and the lack of ability to use savings money are factors that cause economic difficulties in the household.  An introduction to knowledge about household financial management is needed through extension activities. The method of this activity is through a direct communication model with discussion and question and answer sessions.  The aim is to provide understanding, knowledge and skills of the At-taqwa At-taqwa Buaran Cakung Village Group of mothers in managing household finances.  The result of this counseling is that the participants have the knowledge and ability to manage household finances and can apply financial management properly to maintain household economic stability.